2018
DOI: 10.2478/cejcr-2018-0006
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Red Blood Cell Rheology in Sepsis and its Role in Clinical Practice. From Biomolecular Aspects to Possible Therapeutic Interventions

Abstract: Erythrocyte rheology is of interest in understanding microcirculation and oxygen delivery and consumption alterations induced by sepsis and septic shock. Several mechanisms are proposed: (i) direct or indirect RBC membrane alterations, (ii) abnormal intraerythrocytic homeostasis, (iii) RBCs interaction with other cells and extracellular molecules, (iiii) increased reactive species production and altered redox homeostasis. In this review, we describe in part these mechanisms and what’s the impact of these hemor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 183 publications
(243 reference statements)
0
4
0
Order By: Relevance
“…Thus, we consider RDW% a valuable tool in the differential diagnosis of bacterial sepsis and also, an indicator of disease severity and prognosis. Caution should be taken when using RDW as a discriminant, given that its value can be increased in different other conditions and is dependent on RBC transfusion [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we consider RDW% a valuable tool in the differential diagnosis of bacterial sepsis and also, an indicator of disease severity and prognosis. Caution should be taken when using RDW as a discriminant, given that its value can be increased in different other conditions and is dependent on RBC transfusion [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Blood viscosity is a measure of the thickness of blood and is defined as the ratio between the shear stress and shear rate. It may increase in individuals with acute inflammatory diseases due to the increase in acute phase proteins [ 28 ]. HCT % may also alter the blood viscosity.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant supplementation improved the outcome of patients. Thus, erythrocytes can be model cells for the management of sepsis/septic shock to improve the outcome of patients [104]. Larsen et al, 2010, have reported that one of the major causes for sepsis is the increasing levels of free heme released due to hemolysis.…”
Section: Bacterial Infectionsmentioning
confidence: 99%